New Proposed Method For Web Services Security - Muhasin, H. j (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
TI1e Web service securi ty challenge is to understand and assess the risk involved in securing a web-based service today, based on our existing security technology, and at the same time tmck emerging standards and understand how they will be used to offset the risk in new web services. Any security model must i llustrate how data can now through an application and network topology to meet the requirements defined by the busi ness wi thout exposing the data to undue risk. In this paper we propose a mechanism for the client to provide authemication data, based on the service definition , and for the service provider to retrieve those data . We also show how XMl. Digital Signatures and encryption can be exploited to achieve a level of trust.